2020
DOI: 10.1111/febs.15453
|View full text |Cite
|
Sign up to set email alerts
|

Rab family of small GTPases: an updated view on their regulation and functions

Abstract: The Rab family of small GTPases regulates intracellular membrane trafficking by orchestrating the biogenesis, transport, tethering, and fusion of membrane‐bound organelles and vesicles. Like other small GTPases, Rabs cycle between two states, an active (GTP‐loaded) state and an inactive (GDP‐loaded) state, and their cycling is catalyzed by guanine nucleotide exchange factors (GEFs) and GTPase‐activating proteins (GAPs). Because an active form of each Rab localizes on a specific organelle (or vesicle) and recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
267
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 304 publications
(270 citation statements)
references
References 194 publications
(156 reference statements)
1
267
1
1
Order By: Relevance
“…Next, we attempted to identify a specific region(s) of Rab34 that is essential for ciliogenesis by performing mutation and deletion analyses of Rab34-KO cells. In general, Rabs are thought to recognize specific effectors through their switch II region, because mutations of specific amino acids in this region of some Rabs have been shown to abrogate their effector-binding ability (31)(32)(33)(34)(35). Sequence comparisons of the switch II region of mammalian Rabs have revealed that Lys-115 and Cys-116 are specific to Rab34 (and its closest paralog Rab36) (34; Fig.…”
Section: The Unique Long N-terminal Region Of Rab34 Is Required For Cmentioning
confidence: 99%
“…Next, we attempted to identify a specific region(s) of Rab34 that is essential for ciliogenesis by performing mutation and deletion analyses of Rab34-KO cells. In general, Rabs are thought to recognize specific effectors through their switch II region, because mutations of specific amino acids in this region of some Rabs have been shown to abrogate their effector-binding ability (31)(32)(33)(34)(35). Sequence comparisons of the switch II region of mammalian Rabs have revealed that Lys-115 and Cys-116 are specific to Rab34 (and its closest paralog Rab36) (34; Fig.…”
Section: The Unique Long N-terminal Region Of Rab34 Is Required For Cmentioning
confidence: 99%
“…The Rab GTPases are master regulators of intracellular membrane traffic in all eukaryotes (from budding yeasts to humans), and approximately 60 different Rab isoforms are present in mammals (reviewed in Homma et al., 2020; Pfeffer, 2017; Zhen & Stenmark, 2015). Like other Ras‐like GTPases, Rabs function as switch proteins that cycle between a GTP‐bound active state and a GDP‐bound inactive state (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Rab GTPases belong to the Ras superfamily of small GTPases and play important roles in membrane trafficking in eukaryotic cells (reviewed in Hutagalung and Novick, 2011;Zhen and Stenmark, 2015;Pfeffer, 2017;Homma et al, 2020). Like other Ras-like GTPases, Rabs cycle between a GTP-bound active state and a GDP-bound inactive state, and the active Rabs promote various membrane trafficking steps, including vesicle budding, tethering, docking, and fusion, through interaction with their specific effectors.…”
Section: Introductionmentioning
confidence: 99%